Catalytic Ozonation using Iron-Doped Water Treatment Sludge as a Catalyst for Treatment of Phenol in Synthetic Wastewater - Apiradee Sukmilin; Banjong Boonchom; Chalor Jarusutthirak (My University, 2018)
In this study, iron (Fe)-doped water treatment sludge, designated as Fe/WTS, was prepared by a hydrothermal method using phosphoric acid and impregnation with ferric nitrate. The results from X-ray diffraction (XRD) confirmed the presence of Fe loaded on the WTS support, while Brunauer-Emmett-Teller (BET) analysis indicated an increase of specific surface area of the WTS from 37.37 m2/g to 118.51 m2/g after acid modification. The Fe/WTS was successfully used as a catalyst in catalytic ozonation for degradation of phenol in synthetic wastewater. Factors affecting phenol removal efficiency including reaction time, pH, catalyst dosage, and Fe content were investigated. At the optimum condition, i.e., reaction time of 120 min, pH of 11, catalyst dosage of 1 g/L, and Fe content of 2% (w/w), the removal efficiency of phenol was 99.16% which was higher than that of sole ozonation (44.61%). The results of kinetic analyses indicated that the reactions of catalytic ozonation in the presence of Fe/WTS and WTS catalysts followed pseudo-first order kinetic model with rate constants of 0.0362 and 0.0065 min-1, respectively, while that of sole ozone was 0.0046 min-1. This finding presented the potential use of Fe/WTS as a novel catalyst for catalytic ozonation.
Keywords: Phosphoric acid; Advanced oxidation water treatment